Influência da temperatura de solubilização na microestrutura, textura e propriedades de histerese magnética do aço maraging 300 - Oliveira, Francisco José dos Santos (2022)
Maraging steels are ultra-high-strength alloys characterized by low carbon content, high nickel content (about 18%), and lower cobalt, molybdenum, and titanium levels. These steels also have good toughness and machinability in the annealing solution condition, suitable for manufacturing tools such as dies and punches. They are also applied in the aerospace and nuclear industries. In the latter, a package of mechanical and magnetic properties is required in high-rotation motor rotors. Hardening and increased mechanical strength occur due to the precipitation of fine intermetallic compounds in the low-carbon martensitic matrix during the heat treatment known as aging. Aging, however, reduces the tenacity of the alloy. Recent studies have shown that using solubilization temperatures higher than those in everyday use can improve the toughness of Maraging 18%Ni steel. This work carried out solution annealing heat treatments between 820 °C and 1100 °C and aging between 480 °C and 600 °C for 3 hours on maraging steel 300. The magnetic properties were measured using a vibrating sample magnetometer (VSM). Hardness, optical and electron microscopy, previous austenitic grain size measurement, crystallographic texture, and phase quantification (martensite and austenite) by X-ray diffraction were also performed to explain the magnetic response of Maraging 300 steel submitted to the different treatments. The results showed that the grain growth rate of the previous austenite is higher for solution annealing treatments from 1000 °C, promoting a significant increase in martensite packages and blocks. The microstructure of coarse grains after solubilization and aging influenced the saturation magnetization, coercive force, and quadrature ratio of the steel under study. This study also evaluated the behavior of the magnetic properties in the face of heat treatments that improve the toughness of maraging 300 steel.